Estimación de los Costos de Oportunidad para los Emprendedores en la Ciudad De Riobamba, 2022. - Martínez Orellana, Leslie Sarai (2023)
The correct decision-making process for an entrepreneurship is essential in the face of the potential for change that it has adequate administration to counter unemployment and poverty rates in Riobamba. The objective of the research was to estimate the opportunity costs of entrepreneurs in the city of Riobamba in 2022. The research method was deductive, with a causal explicatory level and a quantitative approach. How the survey applied to 162 entrepreneurs was used. The results shows that the food sector is the most performed, were born on the initiative of a third person, with activity between 1 and 2 years ago and located in the parish of Lizarzaburu. The entrepreneurs, mostly with second level of education, started by knowledge of the good or service, without having had any training, with full knowledge in financial, labor, and legal areas. The opportunity cost by income level shows 122 entrepreneurs with a positive value, with $80116.00 being the difference between alternatives; the COs for investment, income tax payment according to the SRI’s classification, mental health, competitive advantages, collaborators, and suppliers show encouraging values for most entrepreneurs. This provokes an acceptance of the hypothesis, demonstrating that adequate decision making has an impact of the entrepreneurs of Riobamba and the well-being of their ventures. For this reason, it is concluded that the CO estimate takes the average value of $453.62, where 162 entrepreneurs gave up 67% less income.